The Concept of Money in an Islamic Perspective - Asyari Hasan; Syifa Mashita; Sheryl Audinata; Alika Firdiya Haya; Raihan Amrulloh (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2023)
This study aims to comprehensively understand the concept of money within the framework of Islamic principles. To achieve this goal, the authors of the articles employ methods that revolve around conducting a thorough examination of the available literature. The data have been obtained from a combination of primary and secondary sources. The study results show that money refers to any openly disclosed and used medium used by leading financial institutions to exchange, measure and store value. In addition, it is important to note that religious teachings do not explicitly mandate the use of gold and silver as a form of currency. However, the academic literature shows that this monetary form exhibits increased stability and a higher level of resistance to inflation when compared to other forms. In accordance with Islamic economic theory, money has three basic functions: first, as a medium of exchange; second, as a mechanism for determining interest rates or valuation; and third, as a means of obtaining loans, provided that they are backed by gold and silver. Â